Nephrotoxicity in HIV-infected/AIDS patients Pathumthani Hospital - Tangchitmeti, Prida (Journal of Medical and Public Health Region 4, 2022)
This study was descriptive and cross-sectional study with sampling of new HIV-infected/AIDS patients. Data were collected between during October 1,2018 - September 30,2020 patient 486 cases from 603 cases (80.59%). The objective of study to determine nephrotoxicity and factor of nephrotoxicity in HIV-infected/AIDS patients Pathumthani hospital. Statistical analyses were conduct to examine factor to nephrotoxicity by adjusted odds ratio (adjusted OR) and confidence interval (95% CI) hypothesis prove with p-value <0.05.The result of study was found 486 new HIV-infected/AIDS patients age between 18-67mean 37.5, 318 men ( 65.4%),112 thin body (35.6%), underlying disease was Diabetes Mellitus 7cases,Hypertension 15 cases, Diabetes Mellitus and Hypertension 4 cases, Dyslipidemia 1 case. The prevalence of nephrotoxicity in HIV-infected/AIDS patients Pathumthani hospital was found 143 cases (29.4 %). Factor to nephrotoxicity including man (adjusted OR=0.538, 95%CI 0.347-0.832, p= 0.005), age≥ 50 years (adjusted OR= 3.803, 95%CI 2.203-6.566, p=0.000) and CD4 cell count < 200 cell/mm3 (adjusted OR= 3.288, 95%CI 2.123-5.093, p=0.000). All HIV-infected/AIDS patients must be advise regarding adverse drug reaction before taking medicine to prevent the severity of symptoms early stage. To concern in risk group for success of cure and good quality of patient life.